2018
DOI: 10.2147/cia.s157584
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and antioxidant effect of Tai chi exercise training in older adults with metabolic syndrome

Abstract: IntroductionThe antioxidant and anti-inflammatory effects of Tai chi (TC) exercise training in healthy older adults has been demonstrated. However, there are no studies on this effect in older adults with metabolic syndrome (MetS).PurposeThe aim of this study was to determine the effect of TC exercise on oxidative stress and inflammatory markers in older adults with MetS.MethodsA quasi-experimental study was carried out with a sample of 110 older sedentary volunteers with clinical diagnoses of MetS: (i) a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 45 publications
2
36
0
1
Order By: Relevance
“…1,3,4,6,9,11 Two quasiexperimental studies were conducted by the same research group. 12,13 Compared with noncontact controls, 6-month t'ai chi practice did not alter circulating levels of inflammatory markers in older adults with periodontal disease, 12 and only lowered levels of one, but not other proinflammatory cytokines in older adults with metabolic disease. 13 These findings are consistent with those from the randomized controlled studies.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…1,3,4,6,9,11 Two quasiexperimental studies were conducted by the same research group. 12,13 Compared with noncontact controls, 6-month t'ai chi practice did not alter circulating levels of inflammatory markers in older adults with periodontal disease, 12 and only lowered levels of one, but not other proinflammatory cytokines in older adults with metabolic disease. 13 These findings are consistent with those from the randomized controlled studies.…”
Section: Resultsmentioning
confidence: 83%
“…Among 26 articles, 13 articles met the inclusion criteria. [1][2][3][4][5][6][7][8][9][10][11][12][13] There were two sets of articles that describe the same studies. 3,4,7,8 The authors combined the two articles for one study, 3,4 and included one article for the other study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, improved biohumoral markers of bone and muscle health correlated with the improvement in muscle relief and performance of physically active participants [32]. Similarly, a study investigating the beneficial effects of Tai-Chi in older adults showed a statistically significant difference in glycosylated haemoglobin levels compared to untrained controls as well as a significant increase in total antioxidant status [25]. Another study evaluating the association between peak oxygen uptake (a marker of aerobic capacity) and metabolic/cardiovascular parameters showed that subjects with lower VO 2 had a higher risk to present altered cardiovascular parameters and had higher levels of accumulation of wide-spectrum acyl-carnitines, alanine, and glutamine [29].…”
Section: Effect Of Pa On Metabolic Parametersmentioning
confidence: 98%
“…Слід відмітити, що активно проводяться дослідження впливу фізичного навантаження на оксидативний та глікаційний стрес. Так, було встановлено, антиоксидантний та гіпоглікемічний ефект тренувань по тайцзи у літніх людей з метаболічним синдромом [43].…”
unclassified